2010
DOI: 10.1002/pbc.22766
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of childhood kaposiform hemangioendothelioma with sirolimus

Abstract: Sirolimus (Rapamune), a mammalian target of Rapamycin (mTOR) inhibitor, which has been used extensively in children following solid organ transplantation, has been demonstrated to have anti-angiogenic activity in pre-clinical models. Limited experience suggests that it may have application to the treatment of vascular lesions. We describe our experience with a 1-year-old female with a kaposiform hemangioendothelioma and Kasabach-Merritt phenomenon who had rapid and dramatic response to sirolimus (0.1 mg/kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 13 publications
2
118
0
9
Order By: Relevance
“…In case of signs of disease recurrence, at present, we do not see any other option but to stay on sirolimus for a number of years to come under close monitoring. Our experience with successful use of sirolimus in a patient with a complex VA is supporting previous reports [4][5][6][7] and encourages further research on this field.…”
Section: Figuresupporting
confidence: 88%
See 2 more Smart Citations
“…In case of signs of disease recurrence, at present, we do not see any other option but to stay on sirolimus for a number of years to come under close monitoring. Our experience with successful use of sirolimus in a patient with a complex VA is supporting previous reports [4][5][6][7] and encourages further research on this field.…”
Section: Figuresupporting
confidence: 88%
“…At present, there is only 1 published retrospective analysis of 6 patients with different VAs and 4 published case reports showing that sirolimus is a potent treatment option for patients with complex VA. [4][5][6][7] In the case of our patient, sirolimus brought a spectacular improvement of his FIGURE 2…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Some recent case reports have shown a rapid response of KHE and KMP to sirolimus [71][72][73]. In a case series reported by Kai et al, sirolimus was shown to be effective in children with refractory KHE with KMS.…”
Section: Role Of Mtor Inhibitorsmentioning
confidence: 99%
“…Bleomycin inhibits the development of HA via inactivation of AKT, which may represent an important therapeutic target for HA (22). Sirolimus, an mTOR inhibitor, has been demonstrated to exert anti-angiogenic activity in kaposifonn hemangioendotheliomas and complicated vascular malformations (23,24). Rapamycin targets the self-renewal and vascular differentiation potential in patient-derived HA stem cells, suggesting a novel therapeutic strategy to prevent formation of HA (25,26).…”
Section: Discussionmentioning
confidence: 99%